The Effect of TGFU, SE ,Combination (TGFU+SE) and Linear Training on Children's Creativity in Futsal - Maryam Davoodi; Rasoul Yaali; Farhad Ghadiri; Aabas Bahram (University of Tehran, 2021)
Finding the best teaching method is an issue that has attracted the attention of many researchers, researchers in behavioral sciences and sports today.. In order to discuss this, the aim of this study was to investigate the effect of TGFU, combination, and SE on individual and team creativity in comparison with the traditional method in futsal games. The statistical population of this study was all children aged 9-12 years in Ahvaz (M age= 10.74 and SD= 1.42). The interventions were designed for futsal skills, so four groups of Participants (20 people in each group) practiced SE, TGFU, combination and linear methods. The test of team and individual creativity was performed using film analysis. Exercises were presented for two months in 16 sessions, one and a half hours each. The results showed that for individual creativity in the post-test, differences between groups were not significant for inappropriate actions but significant for appropriate actions. Also for creative and original actions as well as team creativity TGFU, combination, SE and linear groups had the most progress, respectively. In all variables, the difference between TGFU and linear (p <0.05) and combination and linear (p <0.05) was significant. The results of this study showed the effectiveness of the TFGU and combined methods compared to the linear method, which can be used in schools and kindergartens..